[Overview of Operation Downunder] (Tufts Archival Research Center, 2007)
Materials relating to Operation Downunder. Sums up conclusions of operation, which centers on second hand smoke and preventing government intervention. Provides overview of Downunder operational plan, outlining the situation, the strategy, the benefits, the risks and the tactical plan. Contains results of survey on environmental tobacco smoke.